Die Synodalität in Leben und Sendung der Kirche: eine kritische Erkundung - Hünermann, Peter (Marriage, families & spirituality, 2022)
The article undertakes a critical exploration of the method and theology of synodality, which Pope Francis has made one of the key themes of his pontificate. It examines three central documents that set forth the principles of this approach. First, it looks at the apostolic constitution Episcopalis communio, which provides the legal and administrative framework for all deliberations and decisions leading to the Sixteenth General Assembly of the Synod of Bishops in October 2023. Next, the synod's preparatory document is assessed, which builds on Praedicate evangelium, the 2022 constitution which reorganized the Roman Curia. Finally, it turns to the International Theological Commission's 2018 document Synodality in the Life and Mission of the Church, which sets out the theological basis for the other documents examined. The author concludes that Pope Francis's overall project certainly reveals new potentialities in the documents of Vatican II, especially in Christology and ecclesiology. In regard to canon law and policy, however, he finds there is still a fixation on traditional neo-Scholastic thinking, according to which decision-making power lies exclusively in the sacramentally ordained bishop or pope. The papal power of governance has been given a broader foundation by the synod of bishops, but the aims and guiding principles of synodality have not yet been fully implemented.